Optimalisasi Proses Bisnis Menggunakan Metode Business Process Analysis (BPA) pada PT. XYZ - Eriq Maulana Ishaq; Subchan Asy’ari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
PT XYZ is one of the strategic industries owned by BUMN that produces the main defense equipment for Indonesia's defense system, especially in the maritime sector. In practice, the process of utilizing and managing assets at PT XYZ is in the Asset & Infrastructure Optimization Department which has various operational steps for asset management starting from the asset mapping process to utilizing these assets. This research aims to analyze and optimize business processes in asset management in the Asset & Infrastructure Optimization Department. The research method used is observation and interviews with related parties as well as Business Process Modeling and Notation analysis. The purpose and objective is to provide recommendations in optimizing business processes and increasing efficiency in managing company assets. One of the problems identified was the slow signing and return of agreement letters which caused delays in issuing invoices and payments. Recommendations included creating standard operating procedures, implementing electronic-based contracts and invoices, and utilizing technology for document delivery and storage. Overall, this research aims to improve operational performance and maximize the contribution of PT XYZ's assets to revenue.